YARN essentials : a comprehensive, hands-on guide to install, administer, and configure settings in YARN /: a comprehensive, hands-on guide to install, administer, and configure settings in YARN. (2015) - Fasale, Amol; Nirmala Kumāra, 1943-
No abstract available